2011
DOI: 10.1186/1471-2490-11-11
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy for painful bladder syndrome/interstitial cystitis resistant to conventional treatments: long-term results of a case series in Japan

Abstract: BackgroundThere is no confirmed strategy for treating painful bladder syndrome/interstitial cystitis (PBS/IC) with unclear etiology. Therefore, a pilot study was carried out to evaluate the efficacy and safety of hyperbaric oxygen (HBO) therapy in treatment-resistant PBS/IC patients.MethodsHBO treatment (2.0 ATA for 60 minutes/day × 5 days/week for 2 or 4 weeks) was performed on 11 patients with severe symptoms that had not been improved by previous therapy regimens between December 2004 and July 2009.ResultsS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 20 publications
(20 reference statements)
3
35
1
4
Order By: Relevance
“…Tanaka et al 202 reported successful outcomes in 7/11 patients treated with HBO over 2-4 weeks. Improvements in pain, urgency, frequency, capacity, and symptom scores were maintained for up to 12 months (p<0.05 compared to baseline).…”
Section: Hyperbaric Oxygen (Hbo)mentioning
confidence: 99%
“…Tanaka et al 202 reported successful outcomes in 7/11 patients treated with HBO over 2-4 weeks. Improvements in pain, urgency, frequency, capacity, and symptom scores were maintained for up to 12 months (p<0.05 compared to baseline).…”
Section: Hyperbaric Oxygen (Hbo)mentioning
confidence: 99%
“…3 Recently, Hyperbaric oxygen therapy has been reported to be effective in patients with IC/PBS resistant to conventional treatments. 4,5 Hyperbaric oxygen treatment has clinical effects in different pathological ischemic conditions, eg impaired oxygen delivery or impaired oxygen metabolism. 17 Oxidative stress represents an imbalance between the production of reactive oxygen species (ROS) and the activity of antioxidant defense systems.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Indeed, hyperbaric oxygen therapy has been reported to be effective in patients with IC/PBS resistant to conventional treatments. 4,5 Oxidative stress due to free radicals, which are formed by reperfusion after bladder ischemia, can cause bladder damage. Reperfusion injury is more harmful than the damage caused by ischemia alone.…”
Section: Introductionmentioning
confidence: 99%
“…Tedaviye dirençli bu tür hastalarda ağrı semptom skorunun bir yıl içinde gerilediği ve HBOT'nin iyi tolere edilebilmesine rağmen bir hastada kulak ös-taki tüp disfonksiyonu, 3 hastada ise geri dönüşlü eksüdatif otitis media geliştiğinden söz edilmiştir. 40 van Ophoven ve ark. yapmış oldukları çalış-mada interstisyel sistitli hastalarda HBOT'nin etkinliği ve güvenilirliğini ortaya koymaya çalışmış; 21 hasta ile yaptıkları çift-kör ve "sham" gruplu bir çalışma sonrasında HBOT'nin interstisyel sistitli hastalarda etkin, güvenli ve uygulanabilir olduğunu, semptomlarda azalmayla beraber kontrol grubuna göre önemli iyileşmeler görüldüğünü belirlemişler-dir.…”
Section: İntersti̇syel Si̇sti̇t Ve Ağrili Mesane Sendromuunclassified